The Trouble and Strife Reader - Cameron, Deborah; Scanlon, Joan (Bloomsbury Academic, 2009)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. From 1983 to 2002, Trouble and Strife: The Radical Feminist Magazine was a distinctive voice in British feminism. It was the longest-surviving completely independent feminist periodical published in this period and it combined the intellectual depth of an academic journal with the accessibility, topicality and visual appeal of commercial feminst magazines such as Everywoman and Spare Rib. Featuring articles by internationally prominent feminists including Julie Bindel, Deborah Cameron, Beatrix Campbell, Patricia Duncker, Liz Kelly and Diana Leonard, it represented a particular current in feminism, radical rather than liberal, materialist but not marxist, anti-essentialist but not postmodernist. It regularly challenged orthodoxies on controversial issues such as ritual abuse or the sexual politics of religious fundamentalism. This is a collection of the best and most enduring articles published in the magazine during its 20-year life. It offers a unique historical record of an important strand of radical feminist debate, enabling old readers to revisit it and new readers to discover it.